SCHOOL FACTORS AND ACADEMIC PERFORMANCE OF STUDENTS IN PRIVATE SECONDARY SCHOOLS IN ONDO STATE, NIGERIA - Temiloluwa , Mabel Akinde; Akinrotimi , Iyiomo Oyetakin (International Journal of Allied Sciences (IJAS), 2025)
School factors are issues that can cause changes in strategic management, which could be internal or external to an organization. This study explored the school factors and academic performance of students in private secondary school in Ondo State. Descriptive research design of survey types was used for the study. The population of this study comprises all the principals and teachers in private secondary schools in Ondo State. The study sample size of 168 respondents was used. Questionnaire was used as the instrument for data collection. Research questions were answered descriptively while, hypotheses were tested with Multiple Regression and Pearson Product Moment Correlation at 0.05 level of significance. Result revealed that there was a significant influence of the management factors on the academic performance of students. It also revealed that there was a significant relationship between school facilities and academic performance of students (rcal=0.085;p<0.05) Based on the findings, the study concluded that to ensure high student’s academic performance in any educational institution, effective management factors is required. Therefore, the study recommends that private schools in Ondo State should endeavour to upgrade the management factors in schools for improving the students’ academic performance.